Photopatternable Nanolayered Polymeric Films with Fast Tunable Color Responses Triggered by Humidity. (14th August 2019) - Dong, Ziye; Zhang, Nan; Wang, Yinggui; Wu, Jiangyu; Gan, Qiaoqiang; Li, Wei
Abstract: Smart surfaces that can dynamically respond to environmental stimuli have demonstrated great promise in wearable electronics and optical detectors. Herein, a photopatternable nanolayered polymeric film that can reversibly display and hide structural colors in the visible range in response to relative humidity (RH) changes is reported. This film is fabricated on a silicon substrate using layer‐by‐layer assembly of chitosan and photoreactive carboxymethyl cellulose‐azido derivative, and selectively crosslinked through UV irradiation from a photomask. Compared to crosslinked regions, un‐crosslinked ones swell more and result in a larger thickness at high RH; as a result, those two regions show distinguishable color differences. The correlation of displayed color with film thickness at various RHs is plotted in an International Commission on Illumination (CIE) chromaticity diagram, which is in good agreement with the results obtained from modeling based on the interference theory. It is demonstrated that the structural color patterns on the film can be hidden and displayed spontaneously by contact with humid air, including human breath. This humidity‐triggered color change is fast, of fine resolution, highly reversible, and compatible with most silicon‐based devices. This film is low‐cost, stable, and ready to be applied to large surface areas for potential applications in anticounterfeiting, humidity sensors, and optical color filters. Abstract : A photopatternable nanolayered film that can reversibly display and hide structural colors in response to relative humidity changes is developed. This film is fabricated on a silicon substrate using layer‐by‐layer assembly of chitosan and a photoreactive carboxymethyl cellulose‐azido derivative, and selectively crosslinked through UV irradiation. This humidity‐triggered color change is fast, highly reversible, and compatible with most silicon‐based devices.